2006
DOI: 10.2134/agronj2006.0034
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Amino Sugar–Nitrogen Test on Iowa Soils: II. Field Correlation and Calibration

Abstract: There has been growing interest in using the amino sugar–nitrogen test (ASNT) to improve N fertilization of corn (Zea mays L.). The ASNT is intended to measure the soil organic N fraction that contributes to plant available N. The objectives of this study were to correlate the ASNT to corn N response measures and calibrate the test to Iowa soils and climatic conditions. Soil samples were collected in the fall, early spring, and late spring at the 0‐ to 15‐cm and 0‐ to 30‐cm sample depths. No significant correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
28
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 17 publications
6
28
0
2
Order By: Relevance
“…However, we aimed to raise amino sugar N levels in the HMP soil class to 280 ppm so as to improve the likelihood of establishing soils with high N mineralization. While the ISNT is not a perfect tool for measuring N mineralization potential (Barker et al 2006b;Laboski et al 2008;Osterhaus et al 2008), it has been shown to be useful and is currently the best available approach to predicting mineralization potential (Klapwyk and Ketterings 2006;Lawrence et al 2009;Williams et al 2007). ISNT analyses were performed by university analytical laboratories.…”
Section: Methodsmentioning
confidence: 99%
“…However, we aimed to raise amino sugar N levels in the HMP soil class to 280 ppm so as to improve the likelihood of establishing soils with high N mineralization. While the ISNT is not a perfect tool for measuring N mineralization potential (Barker et al 2006b;Laboski et al 2008;Osterhaus et al 2008), it has been shown to be useful and is currently the best available approach to predicting mineralization potential (Klapwyk and Ketterings 2006;Lawrence et al 2009;Williams et al 2007). ISNT analyses were performed by university analytical laboratories.…”
Section: Methodsmentioning
confidence: 99%
“…Klapwyk and Ketterings (2006) were successful in using the ISNT to predict corn yield response to sidedress N in New York, but only when organic matter (OM) was considered. In contrast to these fi ndings, work from several other states including Iowa (Barker et al, 2006b), Wisconsin (Osterhaus et al, 2008), Virginia (Spargo et al, 2009), Michigan, Minnesota, and Nebraska (Laboski et al, 2008) reported that the ISNT could not accurately predict corn response to N. Th e primary concerns raised in the latter studies involve the relationships between ISNT hydrolyzed-N and total N (TN), crop response to N and EONR. From these concerns emerged the view that the ISNT was not sensitive in measuring potentially mineralizable-N, but rather measured a constant fraction of TN, notwithstanding much evidence to the contrary from data reported by Barker et al (2006a), Laboski et al (2008), Osterhaus et al (2008), and Spargo et al (2009).…”
Section: Predicting Nitrogen Fertilizer Needs For Rice In Arkansas Usmentioning
confidence: 97%
“…Since its development, the Illinois soil N test has been evaluated by many researchers who have reported both successes in using the Illinois soil N test to differentiate N responsive from nonresponsive sites Mulvaney et al, 2006;Sharifi et al, 2007;Williams et al, 2007aWilliams et al, , 2007b and failures (Barker et al, 2006;Laboski et al, 2008;Osterhaus et al, 2008).…”
Section: Illinois Soil Nitrogen Testmentioning
confidence: 99%